2013
DOI: 10.1002/pi.4551
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced interfacial adhesion via interfacial crystallization between sisal fiber and isotactic polypropylene: direct evidence from single-fiber fragmentation testing

Abstract: Bioresource natural sisal fiber (SF) was used to prepare single fiber-reinforced isotactic polypropylene (iPP) composites. Three kinds of interfacial crystalline morphologies, spherulites, medium nuclei density transcrystallinity (MD-TC) and high nuclei density transcrystallinity (HD-TC), were obtained in the single fiber-reinforced composites by implementing quiescent or dynamic shear-enhanced crystallization and by modulating the compatibility interaction between SF and iPP. The development of interfacial sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Specially, the development of interfacial crystallization occurring in the interface between fiber and matrix would enhance interfacial adhesion [14][15][16][17][18][19][20]. It is generally accepted that the interfacial crystallization would substantially influence mechanical behavior [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Specially, the development of interfacial crystallization occurring in the interface between fiber and matrix would enhance interfacial adhesion [14][15][16][17][18][19][20]. It is generally accepted that the interfacial crystallization would substantially influence mechanical behavior [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…GO can be linked to the amino surfaces of glass fiber in the following way: protonation of the amine by the weakly acidic sites of the GO layers (COO − + H 3 NR) and electrostatic attraction between the oppositely charged ions . The graphene on the surface of GF obtained by the chemical reduction can act as nucleating agent to induce interfacial crystallization of polymer and improve the interfacial adhesion …”
Section: Resultsmentioning
confidence: 99%
“…GF/PP IFSS is compared in quenched (no transcrystallinity) and isothermally crystallized material and found that IFSS of transcrystalline specimens was much lower than of the quenched ones. The literature on the IFSS dependency on DoC of PP for carbon and natural (cellulosic) fibers is more broad (see a review of 2005 and later literature); however, analysis of this literature lies out of scope of this article.…”
Section: Introductionmentioning
confidence: 99%